PERAN FAMILY SUPPORT TERHADAP QUALITY OF LIFE DENGAN ISLAMIC RELIGIOSITY SEBAGAI MEDIATOR PADA SISWA BOARDING SCHOOL - Nur Atiqoh, Faiha; Naimah, Tri; Nur’aeni, Nur’aeni; Arnis Grafiyana, Gisella (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Boarding schools implement a 24-hour learning and supervision system that may generate academic, social, and psychological pressures, potentially reducing students’ quality of life (QoL). While numerous studies have examined QoL determinants, few have investigated the mediating role of Islamic religiosity in the relationship between family support and QoL within Islamic residential education. This study aimed to examine the effect of family support on QoL through the mediation of Islamic religiosity among high school students at an Islamic boarding school in Banyumas, Central Java. A quantitative approach was employed using a saturated sampling technique (n = 233). Data were collected through modified instruments: the Brunnsviken Brief Quality of Life Scale (BBQ; CR = 0.932), Perceived Social Support–Family (PSS-F; CR = 0.948), and the Religiosity of Islam Scale (RoIS; CR = 0.943). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4.0. The results revealed that family support significantly influences QoL through the mediation of Islamic religiosity (t = 9.441; p < 0.001). These findings underscore the importance of family involvement in fostering students’ religiosity through regular communication and moral support. This study contributes by presenting an integrative model that combines the influence of external and internal factors on students’ quality of life in an Islamic boarding school setting. ABSTRAK Boarding school menerapkan sistem pembelajaran dan pembinaan selama 24 jam yang berpotensi menimbulkan tekanan akademik, sosial, dan psikologis, sehingga dapat menurunkan quality of life (QoL) siswa. Meskipun determinan QoL telah banyak diteliti, sedikit studi yang menguji peran Islamic religiosity sebagai mediator antara family support dan QoL dalam konteks pendidikan Islam berasrama. Penelitian ini bertujuan menguji pengaruh family support terhadap QoL melalui mediasi Islamic religiosity pada siswa SMA di sebuah pondok pesantren di Banyumas, Jawa Tengah. Metode yang digunakan adalah kuantitatif dengan teknik saturated sampling (n = 233). Instrumen yang digunakan merupakan modifikasi dari Brunnsviken Brief Quality of Life Scale (BBQ; CR = 0,932), Perceived Social Support–Family (PSS-F; CR = 0,948), dan Religiosity of Islam Scale (RoIS; CR = 0,943). Analisis data dilakukan menggunakan SEM-PLS (SmartPLS 4.0). Hasil menunjukkan bahwa family support berpengaruh signifikan terhadap QoL melalui mediasi Islamic religiosity (t = 9,441; p < 0,001). Temuan ini menyoroti pentingnya keterlibatan keluarga dalam mendukung pembentukan religiositas siswa melalui komunikasi rutin dan dukungan moral. Penelitian ini memberikan kontribusi dengan menyajikan model integratif yang menggabungkan pengaruh faktor eksternal dan internal terhadap kualitas hidup siswa di lingkungan pendidikan berasrama berbasis Islam.